2014
DOI: 10.1111/crj.12097
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in patients with cystic fibrosis: a cross‐section study in South Brazil

Abstract: Vitamin D insufficiency is still a problem in CF patients, even in those receiving supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These vitamin D-related effects are relevant to CF because vitamin D deficiency is very common in these individuals (10). Adequate vitamin D status in CF, as determined by blood 25-hydroxyvitamin D [25(OH)D] concentrations, correlates with improved lung function (11,12), reduced pulmonary exacerbations (12) and hospitalizations (13), improved glucose tolerance (14), reduced inflammation (15) and decreased lung bacterial colonization (16). In a pilot clinical trial, we showed that high-dose vitamin D 3 , given to hospitalized CF patients during an acute pulmonary exacerbation, reduced inflammation and improved one-year survival (4,5); however, the impact of underlying vitamin D status and high-dose vitamin D administration on systemic metabolism in CF remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These vitamin D-related effects are relevant to CF because vitamin D deficiency is very common in these individuals (10). Adequate vitamin D status in CF, as determined by blood 25-hydroxyvitamin D [25(OH)D] concentrations, correlates with improved lung function (11,12), reduced pulmonary exacerbations (12) and hospitalizations (13), improved glucose tolerance (14), reduced inflammation (15) and decreased lung bacterial colonization (16). In a pilot clinical trial, we showed that high-dose vitamin D 3 , given to hospitalized CF patients during an acute pulmonary exacerbation, reduced inflammation and improved one-year survival (4,5); however, the impact of underlying vitamin D status and high-dose vitamin D administration on systemic metabolism in CF remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of patients with chronic respiratory disorders also show decreased levels of both vitamin D and calcium (88)(89)(90)(91). This circumstance, which can be partially related to a poor diet intake but also to a reduction in outside physical activities, may induce loss of bone and muscle mass, contributing to muscle dysfunction (89).…”
Section: Vitamin D Deficiencymentioning
confidence: 99%